2016
DOI: 10.1074/jbc.m115.698084
|View full text |Cite
|
Sign up to set email alerts
|

NdhM Subunit Is Required for the Stability and the Function of NAD(P)H Dehydrogenase Complexes Involved in CO2 Uptake in Synechocystis sp. Strain PCC 6803

Abstract: The cyanobacterial type I NAD(P)H dehydrogenase (NDH-1) complexes play a crucial role in a variety of bioenergetic reactions such as respiration, CO2 uptake, and cyclic electron transport around photosystem I. Two types of NDH-1 complexes, NDH-1MS and NDH-1MS′, are involved in the CO2 uptake system. However, the composition and function of the complexes still remain largely unknown. Here, we found that deletion of ndhM caused inactivation of NDH-1-dependent cyclic electron transport around photosystem I and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…Our previous results demonstrated that the NDH-1 assembly intermediates, including NdhH, NdhK, and NdhM, were seriously affected in the DndhM or DndhK mutant (He et al, 2016). Here, we generated a new antibody against NdhJ of Synechocystis 6803 and showed that in the wild type, NdhH, NdhJ, Figure 7.…”
Section: Analyses Of Ndh-1 Assembly Intermediates Under Various Mutanmentioning
confidence: 80%
See 4 more Smart Citations
“…Our previous results demonstrated that the NDH-1 assembly intermediates, including NdhH, NdhK, and NdhM, were seriously affected in the DndhM or DndhK mutant (He et al, 2016). Here, we generated a new antibody against NdhJ of Synechocystis 6803 and showed that in the wild type, NdhH, NdhJ, Figure 7.…”
Section: Analyses Of Ndh-1 Assembly Intermediates Under Various Mutanmentioning
confidence: 80%
“…7). Our recent studies demonstrated that the formation of 100 kD assembly intermediate was not impaired in the DndhI mutant (He et al, 2016). For some unknown reason, Peng et al (2012) could not detect NdhI in the 2D CN/SDS-PAGE in chloroplast stroma.…”
Section: Localization Of Ndhn Ndhh and Ndhj In Ndh-1 Complexesmentioning
confidence: 90%
See 3 more Smart Citations